Clinical-Psychological and Neurophysiological Characteristics of Non-Psychotic Mental Disorders in The Elderly Age (Eurasian Medical Research Periodical, 2022)
This article examines the clinical, psychological and neurophysiological features of non-psychotic mental disorders resulting from brain dysfunction in patients with cerebrovascular pathology, using neurophysiological methods. Research has shown that brain dysfunction develops in patients with cerebrovascular disease. These changes were detected using highly sensitive neurophysiological methods. The use of neurophysiological methods made it possible not only to identify non-psychotic mental disorders and the degree of their impairment, but also to localize pathological disorders in the brain